2011
DOI: 10.1111/j.1365-2702.2011.03906.x
|View full text |Cite
|
Sign up to set email alerts
|

Baby oil therapy for uremic pruritus in haemodialysis patients

Abstract: Applying baby oil is a simple, safe, inexpensive and easily administered treatment for itchy skin in haemodialysis patients. By preventing or reducing uremic pruritus, baby oil treatment may also improve quality of life in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 15 publications
0
43
0
2
Order By: Relevance
“…Dry skin is an important factor for pruritus (6,12,18). We found that patients with dry skin were 3.9 times more likely to suffer from pruritus (p<0.001).…”
Section: No 9 182 Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi mentioning
confidence: 60%
See 2 more Smart Citations
“…Dry skin is an important factor for pruritus (6,12,18). We found that patients with dry skin were 3.9 times more likely to suffer from pruritus (p<0.001).…”
Section: No 9 182 Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi mentioning
confidence: 60%
“…Uremic pruritus is caused in xerosis of the skin and precipitation of the skin divalent ions, secondary hyperparathyroidism, peripheral neuropathy, allergic reactions, hypersensitivity, histamine and atrophy of sweat glands. It is emphasized that age is an important factor of pruritus among the patients who receive hemodialysis treatment, and the intensity and severity of pruritus increase with age (2,3,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xerosis is found in most patients with ESRD and frequently aggravates pruritus. 20,41 Skin hydration with aqueous cream emollient 41 and baby oil 42,43 both have been shown to reduce skin dryness and the severity of UP effectively and to improve patient quality of life when applied two to four times daily. In addition to skin hydration, other topical agents have been used with some success to treat pruritus.…”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, the cornerstone of uremic pruritus therapy is adequate skin hydration. Skin hydration with aqueous cream emollient 73 and baby oil 74,75 have both been demonstrated to effectively reduce skin dryness and the severity of uremic pruritus and improve patient QoL when applied 2 to 4 times daily. There are several small placebo-controlled trials that have shown a significant benefit in uremic pruritus with capsaicin cream, 0.025% to 0.03%, applied 2 to 4 times per day to affected areas.…”
Section: Uremic Pruritusmentioning
confidence: 99%